2008
DOI: 10.1364/ao.47.005654
|View full text |Cite
|
Sign up to set email alerts
|

High resolution digital holographic microscopy with a wide field of view based on a synthetic aperture technique and use of linear CCD scanning

Abstract: Theoretical analysis shows that, to improve the resolution and the range of the field of view of the reconstructed image in digital lensless Fourier transform holography, an effective solution is to increase the area and the pixel number of the recorded digital hologram. A new approach based on the synthetic aperture technique and use of linear CCD scanning is presented to obtain digital holographic images with high resolution and a wide field of view. By using a synthetic aperture technique and linear CCD sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 24 publications
1
59
0
Order By: Relevance
“…(1), the achieved resolution, the SBP, and η for both hologram are shown in Figs. 12(a) and 12(b), and the results from two recent papers [7,14] are shown in Table 1 In conclusion, it was found that the result obtained for the maximum resolution matches well with the expected value. Furthermore, the SBP and the η obtained can compete with the results published in recent papers [7,14].…”
Section: Usaf-1951 Test Targetsupporting
confidence: 67%
“…(1), the achieved resolution, the SBP, and η for both hologram are shown in Figs. 12(a) and 12(b), and the results from two recent papers [7,14] are shown in Table 1 In conclusion, it was found that the result obtained for the maximum resolution matches well with the expected value. Furthermore, the SBP and the η obtained can compete with the results published in recent papers [7,14].…”
Section: Usaf-1951 Test Targetsupporting
confidence: 67%
“…In addition, there have been exciting research efforts into wide FOV imaging systems, including contact-imaging microscopy [5,6], digital in-line holography [7][8][9], focus-grid scanning illumination [10][11][12], and off-axis holography microscopy [13,14]. All these methods try to break the tie between resolution and FOV by abandoning the conventional microscopy design and shifting away from the use of optics schemes that perform optical image magnification.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic aperture imaging is a super-resolution technique originally developed for radio telescopes [46,47]. The concept has also been adopted in microscopy imaging systems in recent years [51][52][53][54][55][56][57]. The basic idea of this technique is to combine images from a collection of telescopes in the Fourier domain to improve the achievable resolution.…”
Section: Macroscopic Imaging Beyond the Diffraction Limit Via Camera-mentioning
confidence: 99%